Comparative analysis of the fatigue contact strength of surfaces hardened by cementation and the ion-plasma nitriding Аvinit N - Sagalovych, Alex; Popov, Viktor; Sagalovуch, Vladislav; Dudnik, Stanislav; Bogoslavzev, Vladimir; Stadnichenko, Nik; Edinovych, Andrey (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports comparative tribotechnical tests of surfaces, hardened by cementation and plasma nitriding Avinit N, for contact fatigue strength at friction in rolling with slipping. Following the cementation, the samples' hardened layer thickness was 1.2 mm; on nitriding, the thickness of the hardened layer was 0.25 mm. The tests were carried out using an acoustic emission method, which is extremely sensitive when registering the transition of tribosystems' operation from the normal (mechanochemical) wear to the initial surface destruction of a fatigue nature. The tests have shown that the average number of cycles before the initial destruction due to fatigue for the samples hardened by the Avinit nitriding technology is 1.82-time higher compared to the cementation-hardened samples. The depth of damage at the surface of the cemented samples could vary between 0.01 and 0.027 mm depending on the diameter of the damage. For the nitrided surfaces, the depth of damage did not exceed 0.003 mm. The samples' resistance to the fatigue wear (destruction) was determined by tests based on 1,000,000 cycles at contact loads σmax=1,140 MPa, typical of medium-loaded surfaces. The test results demonstrated that the integrated multicyclic resistance to fatigue wear (destruction) of the samples, hardened by nitriding, is more than 10 times higher than that of the cementation-hardened samples. The study reported here confirms the effectiveness of using the Avinit ion-plasma nitriding technology instead of cementing, to improve the contact strength of the parts' surfaces. At the same time, worth noting are the advantages of this technology to maintain the size and high quality of surface treatment, which eliminates the need to mechanically finish them after hardening